2017
DOI: 10.1016/j.shaw.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Body Fat Percentage and Fitness among Police Officers: A Statewide Study

Abstract: BackgroundPolice work is generally sedentary although there may be situations that require physical endurance and strength, such as foot chases and arresting suspects. Factors such as excessive body fat can impede an officer's physical ability to deal with such occurrences. Our objective was to examine associations between officers' body fat percentage (BF%) and performance on a standardized fitness protocol.MethodsData were obtained from fitness screening among 1,826 male and 115 female officers in a large US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(84 citation statements)
references
References 24 publications
8
74
0
2
Order By: Relevance
“…Law enforcement is generally seen as a spasmodic profession where sedentary work can be dispersed with a physically demanding occupational tasks (e.g. civilian rescue, suspect pursuit and restraint), and places great physiological stress on those in this occupation (11,25,28,44). As a result, it is important for LEOs to maintain an appropriate level of physical fitness (33,44).…”
Section: Waist Circumference and Waist-to-hip Ratio In Law Enforcemenmentioning
confidence: 99%
“…Law enforcement is generally seen as a spasmodic profession where sedentary work can be dispersed with a physically demanding occupational tasks (e.g. civilian rescue, suspect pursuit and restraint), and places great physiological stress on those in this occupation (11,25,28,44). As a result, it is important for LEOs to maintain an appropriate level of physical fitness (33,44).…”
Section: Waist Circumference and Waist-to-hip Ratio In Law Enforcemenmentioning
confidence: 99%
“…A career within the police force encompasses two conflicting occupational physical requirements, one of which involves sedentary, desk-bound administrative work, and the other involving physically demanding, field-based manual tasks [1]. These physical tasks can include running, jumping, crawling, balancing, vaulting, climbing, lifting, carrying, pushing, pulling, fighting, dragging and restraining a suspect [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was observed that BF correlated with WAnT Pmean in both adolescent and adult female volleyball players [22], where high BF was related to low WAnT Pmean. It has been also shown that a higher BF was related to a lower number of sit-ups in 1 min in female police officers [32]. This negative role of BF for core stability and muscle endurance might be that fat was an extra load that should be sustained without contributing to muscle contraction.…”
Section: Discussionmentioning
confidence: 98%
“…It might be assumed that the intermittent nature of volleyball did not facilitate the development of muscle endurance. The relationship of core stability with BF might be attributed to the negative role of BF in exercise performance related to muscle endurance and anaerobic capacity [22,32]. Previously, it was observed that BF correlated with WAnT Pmean in both adolescent and adult female volleyball players [22], where high BF was related to low WAnT Pmean.…”
Section: Discussionmentioning
confidence: 99%